The perfect gamble [videorecording (DVD)] - Kondilopoulos, Kosta; Arquette, David; Tarantino, Daniella Pick; Miroshnikov, Dean (Well Go USA Entertainment, 2026)
Fresh out of prison, high-rolling gamblers Charlie and Felix risk everything to build an underground casino. As business booms, Charlie falls for their newest hire, Sonia, a sharp-witted woman with a dangerous past. But when the Russian mafia takes notice of their success, the stakes are raised as their dream turns into a deadly game where every bet could be their last.